Upregulated microRNA-143 inhibits cell proliferation in human nasopharyngeal carcinoma - He, Benfu (Oncol Lett, 2016)
The aim of the present study was to investigate the possible functions and mechanism of microRNA (miR)-143 in cell proliferation of human nasopharyngeal carcinoma (NPC). The expression of miR-143 in NPC cells and tissues was investigated using reverse transcription-quantitative polymerase chain reaction. Cell viability assay, colony formation assay and flow cytometry were used to examine the cell proliferative ability and tumorigenicity. The expression levels of p21(Cip1), p27(Kip1), cyclin D1, phosphorylated (p)-retinoblastoma protein (Rb), Rb and cyclin-dependent kinase (CDK) 6 were determined by western blotting. Luciferase assay was used to confirm whether CDK6 was a direct target of miR-143. miR-143 was downregulated in NPC cell lines and tissues. Overexpression of miR-143 in NPC CNE1 cells inhibited proliferation, tumorigenicity and cell cycle progression. Additionally, ectopic expression of miR-143 downregulated cyclin D1 and p-Rb expression, and upregulated p21(Cip1) and p27(Kip1) expression, which subsequently inhibited NPC cell proliferation. It was also observed that CDK6 was a direct target of miR-143, which downregulated CDK6 expression. CDK6 suppression by miR-143 was associated with dysregulated expression of p21(Cip1), p27(Kip1), cyclin D1 and p-Rb, thereby serving an essential role in NPC cell growth. Our findings suggest that miR-143 inhibits proliferation by targeting CDK6, and may aid to identify new targets for anti-oncomiRs.